So, since she weights 6 times more on earth, say for every lb on the moon is 6lbs on earth then.
now, if 1lb on the moon is 6lbs on earth, how much is 90 earth lbs on the moon?
Step-by-step explanation:
open the bracket
6={(1/5×4y) + 1/5×10}
6=4/5y+2
6-2=4/5y
4=4/5y
divide both sides by 4/5
y=1/5
Answer:
25X5
Step-by-step explanation:
If you follow the PEMDAS rule the first thing you must do is the equation inside the parenthesis.
Parenthesis
Exponents
Multiplication
Division
Addition
Subtraction